Інженерна методика розрахунку абразивного зношування теплообмінних поверхонь котла - Yatsenko V.P.; Shraiber O.A.; Troinyak A.O.; Tokarev I.Yu. (General Energy Institute of the National Academy of Sciences of Ukraine, 2009)
We have analyzed the existing methods of calculating the ash-induced wear of convective heat-transfer surfaces of a boiler. Generalized dimensionless relations for finding the sedimentation coefficient and velocity of ash particles at their interaction with heat-transfer tubes of an economizer bundle have been obtained. We propose a simplified method for calculating the wear of tubes. Results of testing calculations of wear rate are given at burning of some coal grades.